Preliminary Design of Floating Photovoltaic at The Logung Dam - Ananda, Rifqi Firza; Budiarto, Rachmawan; Prabowo, Irawan Eko (2022)
A Floating Photovoltaics (FPV) is one type of solar power plant installation with promising performance. This power plant will be designed on the Logung dam with an on-grid system on a 5 MWp scale. This research focused on the analysis of the potential and feasibility of the site, configuration of the FPV components, and system performance. The site analysis was focused on solar radiation, weather, accessibility, and bathymetry. The component configuration is selected based on solar panel and inverter as independent variables. Based on performance specification, the research selected three brands of photovoltaics and two of inverters. The potential analysis showed that the average Global Horizontal Irradiance (GHI) was 5,14 kWh/m2 in the last 10 years. The site is characterized with its good accessibility, sufficient water depth ranging from 70 m to 90 m, and water level fluctuations from 62,46 m to 93,20 m. The selected configuration of floating solar power plant components consist of 12240 panels (450Wp) arranged in 15 series and 816 string solar panels, 51 DC combiner box 100 kW, 100 kW inverter, DC cable between solar panels to the inverter, AC cable between inverter to power grid type NYYHY, floater and mounting system made from HDPE and aluminum, deadweight anchor type, and mooring type loose capstan rope. The design shows a predicted system performance with a capacity factor of 18,61 , system efficiency of 17,51 , and a performance ratio of 83,75. © 2022 IEEE.